Restoring, Repairing, and Regenerating Tissues through Biomaterials, Cells, Scaffolds, and Innovative Technologies - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben (African Journal of Medicine, Surgery and Public Health Research, 2025)
Tissue engineering and regenerative medicine (TERM) is an innovative area of research and development that includes biomaterials, cells, scaffolds, scaffolding structures, and even bioactive substances to restore, repair or regenerate damaged tissues along with organs. The scope of synthetic skin expansion has now progressed to engineering kidneys, hearts, and lungs. Use of stem cell therapies or extracellular matrices for organ healing and regeneration are other; notable shifts toward tissue engineering paradigm are towards healing adn regeneration rather than the development of reconstructive surgery. While research has shown promise, there are still concerns regarding its clinical use citing complications such as immune system rejection of newly implanted tissues, ethical issues and the economical creation of engineered tissues. The efforts being made in Asia demonstrate emerging potential in TERM. Enhanced collaboration across disciplines is essential to pave new ways towards realizing current restrictions and bold influencing ideas alongside breakthroughs.